Felicity Meakins and Patrick McConvell. 2021. A grammar of Gurindji as spoken by Violet Wadrill, Ronnie Wavehill, Dandy Danbayarri, Biddy Wavehill, Topsy Dodd Ngarnjal, Long Johnny Kijngayarri, Banjo Ryan, Pincher Nyurrmiari and Blanche Bulngari - Majewicz, Alfred F. (Lingua Posnaniensis, 2021)
Review of: Felicity Meakins and Patrick McConvell. 2021. A grammar of Gurindji as spoken by Violet Wadrill, Ronnie Wavehill, Dandy Danbayarri, Biddy Wavehill, Topsy Dodd Ngarnjal, Long Johnny Kijngayarri, Banjo Ryan, Pincher Nyurrmiari and Blanche Bulngari (Mouton Grammar Library 91) Berlin–Boston: De Gruyter Mouton, pp. xxxii + 746